Eksplorasi Bakteri Kandidat Probiotik di Lumpur Hutan Mangrove Wonorejo [Exploration The Candidate Probiotic Bacteria In Mangrove Mud Wonorejo] - Rahayu Kusdarwati; Indah Pratiwi; Wahju Tjahjaningsih (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
AbstractMangrove as one of the bacterial community development area, one of which is a probiotic bacterium. Exploration of probiotic bacteria in the mud of mangrove forest has not been done, especially in the mud in the mangrove forest Wonorejo, Rungkut-Surabaya.  This study aims to determine the candidate probiotic bacteria species found in mangrove forests Wonorejo. This research method is descriptive in the form of sludge sampling surveys at five different points area. Sampling points are T1, T2, T3, T4 and T5. T1 is an area of mangrove forest near Wonorejo milkfish. T2 is a region of southern estuarine mangrove forest near Wonorejo milkfish. T3 is a region of northern estuary mangrove forest Wonorejo near sewerage drains Wonorejo citizens. T4 is a region of southern estuarine mangrove forest Wonorejo and T5 is a region of northern estuarine mangrove forest Wonorejo. Fifth sludge samples performed a series of tests in the identification bekteri Hall Fish Quarantine, Quality Control and Safety of Fishery Products Class 1 Juanda. Data were analyzed by descriptive identification results by describing the data distribution of probiotic bacteria at each sampling point area Wonorejo mangrove mud.  The results showed that probiotic candidate bacterias found were Bacillus sp., B. subtilis, B. licheniformis, Pseudomonas sp., P. pseudomallei, Vibrio alginolyticus and Microccus sp.